The Social Integration of the Displaced Who Live in Camps: A Socio-anthropological Study: Al-Anbar as a Model - Mohammed, Muayad Manfi (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims at determining the existence of social integration among the displaced in camps within Anbar Governorate. It follows the socio-anthropological approach. It relies on the means of collecting information, the most prominent of which are: observation by participation, interview, records and informants. while the sample is a random sample of (100) individuals to obtain basic information and data that cannot be obtained through other means,